Serum IgG Responses to gp15 and gp40 Protein-Derived Synthetic Peptides From Cryptosporidium parvum - Urrea-Quezada, Alejandro; Balmaceda-Baca, Ruben; Garibay, Adriana; Hernández, Jesús; Valenzuela, Olivia (Frontiers in Cellular and Infection Microbiology, 2022)
Cryptosporidium spp. are responsible for moderate to severe diarrhea, mainly in children and immunocompromised patients. Using ELISA, the recognition of synthetic peptides generated from the sequences of the Cryptosporidium parvum gp40 and gp15 proteins by serum IgM and IgG antibodies from patients infected (cases) with Cryptosporidium hominis, C. parvum, and Cryptosporidium canis, and uninfected individuals (controls) was evaluated. A statistically significant difference (p = 0.0025) was found in terms of the recognition of peptides A133 and A32 between cases and controls. Additional studies are necessary to understand the potential of these peptides as vaccine candidates.